(untitled) (Trabalho & Educação, 2018)
The purpose of the present study is to expose the emancipatory potential of Pedagogy of Alternation within the Tabocal Agricultural Family School (EFA-Tabocal), located in the Primavera Community - São Francisco - Minas Gerais. Ethnographic research was chosen to meet the purpose of the study. Electing Alternation as the object of analysis, the researcher assumed to adopt the path of alternation in the Gerais area of Minas Gerais. School time and community time dictated time and space of the research. Therefore, it was necessary to track the path of the students and to recognize what the subjects involved in the educational process of alternation say about it. It was observed that Pedagogy of Alternation is not limited to school time and community time, but forged by both "times" and in several places... ___ O presente estudo buscou revelar o potencial emancipatório da Pedagogia da Alternância no âmbito da Escola Família Agrícola de Tabocal (EFA-Tabocal), localizada na Comunidade Primavera no município de São Francisco - Minas Gerais. Para atender ao propósito deste estudo, optou-se pela pesquisa do tipo etnográfica. Ao eleger a Alternância como objeto de análise, o pesquisador se comprometeu em adotar o caminho da alternância pelo Gerais Mineiro. Tempo Escola e Tempo Comunidade ditaram o tempo e o espaço da pesquisa. Foi necessário fazer o caminho dos alunos, e reconhecer nestes tempos o que os sujeitos envolvidos no processo educativo da Alternância têm a dizer sobre ela. Observou-se que a Pedagogia da Alternância não se resume aos dois tempos, mas, forja-se em dois tempos e vários lugares...